THE POTENTIAL OF PSYCHOSOCIAL HEALTH INDICATORS THAT EFFECTS TO CHRONIC RENAL FAILURE (CRF) PATIENT WITH COGNITIVE BEHAVIOR THERAPY (CBT) BASED - Tutu April Ariani (Jurnal Kesehatan Hesti Wira Sakti, 2017)
Introduction: Chronic Renal Failure (CRF) is classified as a chronic disease that is due to take place throughout the life of the patient. Stress experienced by patients occur due to patient awareness that the disease can’t be cured, the patient difficulty adapting to the conditions and limitations experienced by many patients. Cognitive Behavior Therapy (CBT) is a therapy used to modify thoughts, feelings and behaviors by emphasizing the role of brain to analyzing, deciding, asking, doing and deciding so that it can change the feelings and thoughts from maladaptive become adaptive. Methods: This study included quasy experimental research. The method used the provision of CBT intervention and FGD (Focus Group Discussion) through 5 sessions. Data collection was done by means of interviews, questionnaires and participatory techniques. Results: Wilcoxon test for depression scale get p (0.00) < (0.05) and self efficacy p (0.00) < (0.05). As for the self-esteem of data analyzed by the McNemar test get p (0.00) < (0:05). Discussion: There is a change in degree of decreased depression psychosocial as well as increased self-efficacy and self-esteem. Result of statistical analysis shows significant differences between before and after the intervention CBT. This can happen because the CBT helps individuals to identify thoughts and beliefs are dysfunctional, negative, no correct and self-critical characteristic and transform them into positive thoughts.